PENGARUH PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PADA PENGGUNAAN SMARTPHONE SAMSUNG (Studi pada Mahasiswa Universitas Diponegoro) - Andre Haryanto; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2021)
Abstract: The decline in the market share of Samsung smartphone was due to the defeat of Samsung with Samsung smartphone competitors in terms of price and product quality on Samsung smartphones. The purpose of this study was to determine the effect of price perception on customer satisfaction on Samsung smartphone product, determine the effect of product quality on customer satisfaction of Samsung smartphone product, determine price perception and product quality in customer satisfaction on smartphone product. This type of research is explanatory research. The research method used is the Non-Probability Sampling technique with the snowball sampling method. By using a questionnaire and google form as data collection methods. Data processing using SPSS 25.0. The samples collected were 97 respondents who used Samsung smartphone type M. the data analysis used was correlation test, simple linier regression test, multiple linier regression test, t test and f test. Based on the results of the analysis, it can be concluded the perception of price and product quality has a positive and significant effect on customer satisfaction. The suggestion put forward in this study is that Samsung smartphones reduce prices and improve product quality, making consumers choose Samsung and increasing the performance of RAM, CPU, GPU and Storage.Keywords: Smartphone; Price Perception; Product Quality; Customer Satisfaction